The Influence of Capital Structure and Operational Efficiency on the Financial Performance of Mining Sector Companies on the IDX: Green Innovation as A Moderator - Agus Nugroho; JMV Mulyadi; Shanti Lysandra; Syahril Djaddang (Publikasi Indonesia, 2025)
The mining industry faces increasing pressure to balance financial performance with environmental sustainability. This study aims to analyze the effect of capital structure and operational efficiency on financial performance, as well as to examine the role of Green Innovation as a moderating variable in mining sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2019–2023. Financial performance is measured using Return on Assets (ROA), capital structure is measured by Equity Ratio (ER), operational efficiency is assessed through Total Asset Turnover (TATO), and green innovation is measured based on sustainability reporting indicators (GRI). This research adopts a quantitative approach using the WarpPLS analysis method. The results of the analysis indicate that capital structure has a positive and significant effect on ROA, and operational efficiency also has a positive and significant effect on ROA. Furthermore, green innovation is found not to moderate the effect of capital structure on ROA, but does moderate the effect of operational efficiency on ROA in a positive and significant direction. These findings indicate that green innovation plays an important role in strengthening or weakening the relationship between internal financial variables and the company's financial performance. Therefore, mining sector companies are advised to consider integrating green innovation into their financial strategies to enhance long-term sustainability and profitability.